2011
DOI: 10.1007/s00134-011-2130-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the MIC of vancomycin and clinical outcome in patients with MRSA nosocomial pneumonia

Abstract: About half of the MRSA isolates had high vancomycin MIC. Patients infected with these strains showed slower clinical response and higher relapse rate than patients infected with low vancomycin MIC isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 29 publications
2
45
2
1
Order By: Relevance
“…In agreement with our findings, MRSA-related pneumonia has been reported to cause high mortality rates [19,20] . Furthermore, these patients were mostly aged and presented with various underlying diseases such as diabetes mellitus, hypertension and end-stage renal failure.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our findings, MRSA-related pneumonia has been reported to cause high mortality rates [19,20] . Furthermore, these patients were mostly aged and presented with various underlying diseases such as diabetes mellitus, hypertension and end-stage renal failure.…”
Section: Discussionsupporting
confidence: 93%
“…Although vancomycin MICs Յ 2 g/ml are considered to represent susceptibility, treatment of invasive infections due to MRSA strains with drug MICs ranging from 1 to 2 g/ml has had a lower success rate than treatment of infections due to strains with drug MICs Յ 0.5 g/ml (9, 41). Despite reports over the past several years of MRSA isolates displaying reduced vancomycin susceptibility ("MIC creep") (9,45,46,51), others have demonstrated MIC stability in the setting of low vancomycin consumption (2). More recently, data from a large U.S. multicenter study suggested that reports of MIC creep may be exaggerated and that it perhaps poses less of a widespread problem than the reports have indicated (40).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the infections caused by VISA often result in poor clinical outcomes in patients treated with glycopeptides. [1][2][3] Phenotypically, VISA isolates exhibit several common characteristics such as thickened cell walls, 4 reduced autolysis 5 and attenuated virulence allowing immune escape and long persistence. 6 However, the genetic mechanisms responsible for reduced vancomycin susceptibility in VISA vary.…”
Section: Introductionmentioning
confidence: 99%